Diluent Effects in the Solvent Extraction of Rhenium (Vii) with Amine Extractants in [Tf2n]-Based Ionic Liquids: Experimental and Cosmo-Rs Analysis - Romero-Figueroa, J; Quijada-Maldonado, E; Araya-Lopez, C; Olea-Chandia, F; Villarroel-Utreras, E (Elsevier B.V., 2022)
In this work, the factors that determine a high or low extraction performance when using ionic liquids (ILs) as diluents in the solvent extraction of Rhenium (Re(VII)) from aqueous solutions were studied by means of experiments, quantum chemical (QC) calculations, and COSMO-RS. For this purpose, kerosene and the ionic liquids (ILs) 1-butyl-3-methyl-imidazolium bis(trifluoromethylsulfonyl)imide [C4C1im][Tf2N], or 1-methyl-3-octylimidazolium bis(trifluoromethylsulfonyl)imide [C8C1im][Tf2N] were used as diluents to determine de effect of alkyl chain of ILs, and two high molecular weight amines: trioctylamine (TOA) and Alamine 336 (Al336) were used as the extractants. The results indicated that the so-called reference extracting phase TOA in kerosene achieved 99% extraction percentages. On the contrary, a lower performance was observed when replacing kerosene with any of both ILs. This reduction was mainly due to two reasons. First, the IL dissociates where the cation takes part in the formed complex, hindering the TOA-perrhenate bonding, and second, the formed complex that contains IL cations shows poor dissolution in the diluent phase. This could be avoided by means of long alkyl chain imidazolium bis(trifluoromethylsulfonyl)imide-based ILs. Additionally, operating parameters such as equilibrium stages and concentration of the stripping agent were studied. Promising results were obtained by replacing TOA with Al336 dissolved in the IL [C8C1im][Tf2N], showing very similar results with the reference extracting phase. © 2021 Elsevier B.V.